Strategy for Instilling Local Wisdom Values in the Formation of Students' Morals - Rasdia, Rasdia; Hernah, Hernah (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: This study aims to determine how morals are formed through instilling local wisdom values ​​in students and how to internalize local wisdom values. Methodology: This type of research uses field research. Data collection and processing techniques through direct observation, interviews and documentation from the Principal, Teachers, and students at Elementary School 251 Pinrang. Triangulation as a test of data validity that utilizes something else from outside the data for data comparison, with data analysis techniques, namely data reduction, data presentation, and drawing conclusions from the data obtained. Main Findings: The results of this study indicate that the formation of morals that is continuously carried out by educators through the instillation of local wisdom values ​​in activities inside and outside the classroom that get a positive response from students and are implemented in everyday life in the values ​​of Pappaseng culture theoretically and practically also contain Islamic teachings that remain in harmony and in accordance with the basic guidelines of Muslims, namely the Qur'an and Hadith. It can be seen from its application that it can really form the morals of students with the method of exemplary behavior, habituation and advice. Thus it can be concluded that the instillation of local wisdom values ​​in the formation of student morals at State Elementary School 251 Pinrang is going well and is accepted by students with the actualization of good morals and positive responses. Novelty/Originality of this study: This study provides a new contribution by revealing how the instillation of local wisdom values, especially the Pappaseng culture, plays a significant role in the formation of students' morals in elementary schools.